2014
DOI: 10.17557/tjfc.40243
|View full text |Cite
|
Sign up to set email alerts
|

First Report on The Occurrence and Symptomatology of Phyllody Disease in Jute (Corchorus olitorius L.) and Its Plant Characteristics in Turkey

Abstract: Although jute (Corchorus olitorius L.) is treated as a weed in Turkey, it is cultivated and harvested for its fiber, tender shoots, and leaves in Africa and Asia. We report the occurrence and symptomatology of phyllody disease in jute observed for the first time in 2010 during our studies focusing on sesame phyllody in an experimental field at the Akdeniz University Campus, Antalya, Turkey. The disease was also observed in the following two years, 2011 and 2012. In the top of the infected jute plant, the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, the most plausible approach strategically is that prophylactic methods restricting the expansion dissemination of these agents may be more usable and sustainable. Control of weeds or insects is important for inoculum formation, its transmission and disease development (Cagirgan et al, 2014). Further studies are needed to determine the distribution, inoculum sources and insect vectors of 'Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most plausible approach strategically is that prophylactic methods restricting the expansion dissemination of these agents may be more usable and sustainable. Control of weeds or insects is important for inoculum formation, its transmission and disease development (Cagirgan et al, 2014). Further studies are needed to determine the distribution, inoculum sources and insect vectors of 'Ca.…”
Section: Discussionmentioning
confidence: 99%
“…The mallow (molokhia) plants (Corchorus olitorius L.), also known as Jew's mallow, wild okra, jute mallow, or tossa jute, are primarily herbaceous perennials from edible leafy vegetables or fiber crop in the Malvaceae family and present naturally in the Mediterranean (Cagirgan et al, 2014;Abdel-Razek et al, 2022). With a 2.45tons/ha productivity, Egypt's 887 hectares of jute mallow farming produced about 2173 tonnes of output (Haridy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this plant plays a relevant role in maintaining human health, and the plant possesses a wide range of biological activities connected to its phytochemical composition (Moerman, 1996;Hussien et al, 2017;Abdel-Razek et al, 2022) as the leaves of C. olitorius include minerals, vitamins, and phenolic compounds that are abundant in plants (Schipper, 2000;Abdel-Razek et al, 2022). The leaves are used in herbal pharmacopeia (Adebo et al, 2018) to treat gonorrhea, pain, fever, tumors, an emollient, diuretic, and dysentery (Ndlovu & Afolayan, 2008;Abdel-Razek et al, 2022) and preventing the risk of Alzheimer's disease (Mangione et al, 2022) or as a potential substitute for the generation of biofuel (Cagirgan et al, 2014). Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Holm et al (1997), this species is a weed in 50 countries and in 28 crops. For instance in Turkey, this species is observed as weed in summer crops like sesame, citrus and olive groves in the southern provinces such as Antalya, Adana and Hatay of the Mediterranean Region of Turkey (Incekara 1979;Uremis 2005;Kitis 2009;Cagirgan et al 2014).…”
Section: Introductionmentioning
confidence: 99%